Penerepan Metode Mediated Learning Experience (MLE) pada Ibu dengan Anak Usia 5-6 Tahun untuk Meningkatkan Kualitas Interaksi dalam Kegiatan Pendampingan Belajar - Dzulfadhilah, Fitriani; Amriani, Sri Rika; Lismayani, Angri; Asti, A. Sri Wahyuni (Universitas Negeri Malang, 2023)
This study aims to determine the effect of applying the Mediated Learning Experience (MLE) method on mothers with children aged 5-6 years to improve the quality of interaction in learning assistance activities. The research approach used is quantitative with pre-experimental types. The research design used was single-group, pretest-posttest. The population of this study was all students at Nadira Kindergarten, Takalar Regency. The sampling technique used to obtain samples was purposive sampling so the subjects in this study were 7 children aged 5-6 years. The data collection technique used in this study was the NST questionnaire, interviews, and Mediated Learning Experience Rating Scale (MLERS) instrument. The analysis technique used is descriptive statistical analysis and nonparametric statistical analysis using the Wilcoxon test. The results of hypothesis testing using the SPSS version 22 application, show that the data Asymp (2-tailed) = 0.018 <0.05, then Ha is accepted and H0 is rejected. The results showed that there was an effect of applying the Mediated Learning Experience (MLE) method on mothers with children aged 5-6 years to improve the quality of interaction in learning assistance activities.